Cross-cultural features of international tourism - Bahorka, Mariia; Багорка, Марія Олександрівна; Kvasova, Liudmila; Квасова, Людмила Сергіївна (Економічна академія ім. Ценова, Свіштов, Болгарія, 2023)
The article deals with the problems of "cross-cultural shock" that arise in any international company. In particular, the work offers an analysis of cross-cultural differences of Western and Eastern cultures in comparison with Ukrainian national peculiarities. The matrix of features of personnel management in different cultures and three models of the international manager's competence are considered. An adaptive cross-cultural training scheme for multinational companies operating in the Ukrainian market has been created and tools are proposed for active use, allowing to reduce the level of cultural contradictions. У статті розглядаються проблеми «міжкультурного шоку», які виникають у будь-якій міжнародній компанії. Зокрема, у роботі пропонується аналіз міжкультурних відмінностей західної та східної культур у порівнянні з українськими національними особливостями. Розглянуто матрицю особливостей управління персоналом у різних культурах та три моделі компетенції міжнародного менеджера. Створено схему адаптивного крос-культурного навчання для транснаціональних компаній, що працюють на ринку України, та запропоновано інструменти для активного використання, що дозволяють знизити рівень культурних протиріч.
Крос-культурні особливості міжнародного туризму
Keywords: cross-cultural models; крос-культурні моделі; cultural contradictions; культурні протиріччя; international management; міжнародний менеджмент; management; менеджмент